2018
DOI: 10.1007/s11136-018-2028-8
|View full text |Cite
|
Sign up to set email alerts
|

What matters most to sepsis survivors: a qualitative analysis to identify specific health-related quality of life domains

Abstract: Purpose It is unknown how sepsis survivors conceptualize health-related quality of life (HRQL). We aimed to identify important HRQL domains for this population. Methods A literature search was performed to inform an interview guide. Open-ended interviews were held with 15 purposefully sampled sepsis survivors. Interview transcripts were analyzed by interpretative phenomenological analysis to allow themes to develop organically. Resulting codes were reviewed by an independent expert. The preliminary list of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 38 publications
5
43
1
2
Order By: Relevance
“…The participants in this study experienced that they were left alone to cope with the consequences after returning home. Previous research has been focused on critically ill patients post ICU [39,35,30,[40][41][42], however all of the sepsis survivors in this study, post ICU or not, describe similar symptoms of sequelae. In light of the fact that much is unknown about PTSD in connection with the survival of critical illness, the dynamics of recovering physically and psychologically are important factors to consider when planning the care for the sepsis patients [43,44].…”
Section: The Psychological Impact On Lifementioning
confidence: 95%
“…The participants in this study experienced that they were left alone to cope with the consequences after returning home. Previous research has been focused on critically ill patients post ICU [39,35,30,[40][41][42], however all of the sepsis survivors in this study, post ICU or not, describe similar symptoms of sequelae. In light of the fact that much is unknown about PTSD in connection with the survival of critical illness, the dynamics of recovering physically and psychologically are important factors to consider when planning the care for the sepsis patients [43,44].…”
Section: The Psychological Impact On Lifementioning
confidence: 95%
“…the future achievements of bioinformatics or omics techniques, 21,22 as in cancer, 23,24 in liver and digestive disease 25 and in environmental and infection-related disease, 26 but also by point-of-care direct imaging and insight for the prevention of the possible emerging source of dissemination. 27 A realistic perception of disease is the basis for a strong agreement and alliance of doctors and patients against diseases that have many hidden effects. This is a key component for better coping with post-sepsis psychological and social consequences and for reducing the area of misunderstanding between health professionals and patients.…”
Section: Advice and Sustainable Actionsmentioning
confidence: 99%
“…This is a key component for better coping with post-sepsis psychological and social consequences and for reducing the area of misunderstanding between health professionals and patients. 27 Support of patients with such severe diseases should not be only "consolatory", because such interventions may unmask the real needs and the quest for most appropriate potentially available expertise. 28 Standard sepsis education projects for clinical practitioners should be optimally established and well performed.…”
Section: Advice and Sustainable Actionsmentioning
confidence: 99%
“…There were no significant differences in the number of reported problems with mobility (sepsis 37.8% vs. non-sepsis 38.7%, p = 0.86), ability to perform self-care (24.7% vs. 26.0%, p = 0.44), pain/discomfort (42.4% vs. 41.6%, p = 0.54) or anxiety/depression (36.9% vs. 37.7%, p = 0.68) at 6 months. In a qualitative study of HRQL, the sepsis survivors reported difficulties with psychological disorders, fatigue, physical impairment, coping with daily life, ability to walk, return to normal living, cognitive impairments, self-perception, and control over life [8].…”
mentioning
confidence: 99%